Validation of high voltage power supplies for the 1-inch photomultipliers of AugerPrime, the Pierre Auger Observatory upgrade. (1st April 2022) - Anastasi, G.A.; Buscemi, M.; Aglietta, M.; Caruso, R.; Castellina, A.; Costa, S.; Gallian, S.; Gorgi, A.; Guardone, N.; Lombardo, C.; Wheadon, R.; Zampieri, A.
Abstract: In the framework of the upgrade of the Pierre Auger Observatory, a new high voltage module is being employed for the power supply of the 1-inch photomultiplier added to each water-Cherenkov detector of the surface array with the aim of increasing the dynamic range of the measurements. This module is located in a dedicated box near the electronics and comprises a low consumption DC-DC converter hosted inside an aluminum box. All the modules have undergone specific tests to verify their reliability in the extreme environmental conditions of the Argentinian pampa. In this paper, we describe the validation procedure and the facility developed to this aim. The successful results of the tests on the HVPS modules are presented and discussed.